1998
DOI: 10.1177/019262339802600512
|View full text |Cite
|
Sign up to set email alerts
|

T-2 Toxin-Induced Apoptosis in Hematopoietic Tissues of Mice

Abstract: We examined T-2 toxin-induced lesions in the bone marrow and splenic red pulp as many as 48 hr after oral inoculation with 10 mg/kg body weight of T-2 toxin in female ICR:CD-1 mice. Histopathologically, the bone marrow and splenic red pulp showed a significant hypocellularity. In the bone marrow, the number of myelocytes significantly decreased due to the loss of immature granulocytes, erythroblasts, and lymphocytes. The nuclei of the remaining cells showing pyknosis or karyorrhexis were positively stained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 23 publications
1
38
0
2
Order By: Relevance
“…Our reseach group first clarified that T-2 toxininduced death of lymphocytes in the thymus 6,7 , splenic white pulp 6,7 and Peyer's patches 8 is apoptosis. After that, our research group also confirmed that hematopoietic cells in the bone marrow and splenic red pulp 9 , and intestinal crypt epithelial cells 10 die through apoptosis following T-2 toxininoculation.…”
Section: Introductionsupporting
confidence: 54%
“…Our reseach group first clarified that T-2 toxininduced death of lymphocytes in the thymus 6,7 , splenic white pulp 6,7 and Peyer's patches 8 is apoptosis. After that, our research group also confirmed that hematopoietic cells in the bone marrow and splenic red pulp 9 , and intestinal crypt epithelial cells 10 die through apoptosis following T-2 toxininoculation.…”
Section: Introductionsupporting
confidence: 54%
“…In the present study on rats, single cell necrosis was observed in the nervous system and liver of fetuses. Single cell necrosis of hematopoietic cells in the fetal liver was considered to be similar to that in the spleen and bone marrow in mice treated with T-2 toxin 26 . It has been considered that fetotoxicity of T-2 toxin is secondary to maternal toxicity 13 .…”
Section: Discussionmentioning
confidence: 99%
“…4). On the other hand, mature granulocytes show no significant changes 27 . Such changes in the hematopoietic tissues result in a significant depression in the number of white blood cells in peripheral blood [27][28][29] .…”
Section: Hematopoietic Tissuesmentioning
confidence: 97%
“…On the other hand, mature granulocytes show no significant changes 27 . Such changes in the hematopoietic tissues result in a significant depression in the number of white blood cells in peripheral blood [27][28][29] . The spleen, which is composed of white and red pulp, is the largest lymphoid tissue in the circulation, and it is the site of erythrocyte storage and the removal of dysfunctional erythrocytes and leukocytes.…”
Section: Hematopoietic Tissuesmentioning
confidence: 97%